Glue wood veneer to wood-fiber–high-density-polyethylene composite. (December 2019) - Sun, Yanan; Guo, Limin; Liu, Yinan; Wang, Weihong; Song, Yongming
Abstract: Wood-fiber-reinforced thermoplastic plastic composite is a type of environmentally friendly material. However, its application in furniture and interior decoration is limited due to its lack of wood texture. In this work, wood-veneer-facing decoration was explored to beautify the composite's appearance. Surface planning and slight sanding were applied to wood-fiber–high-density-polyethylene (WF-HDPE) composite. Polyvinyl acetate emulsion was used as adhesive, and the veneer-faced WF-HDPE composite floor was prepared by the hot-pressing method. The bonding line was analyzed with Fourier-transform infrared spectroscopy and scanning electron microscopy. Planning plus sanding treatment removed the HDPE film on the composite surface and exposed the wood fibers to react with the adhesive. The rough surface provided all decorative samples bonding strengths higher than 0.9 MPa. The bond line could stand 63 °C water soaking for 3 h without delamination. The hot-pressing temperature exhibited a significant effect on surface bonding strength. The optimized hot-pressing technique included a hot-pressing temperature of 80 °C, a hot-pressing time of 10–20 min, and a hot-pressing pressure of 0.2 MPa. With this combination, the surface-decorative veneer retained the beauty of its original color.